Non-Adhesive Liquid Embolic Agents in Extra-Cranial District: State of the Art and Review of the Literature - Filippo Piacentino (MDPI AG, 2021)
This review focuses on the use of “new” generation of non-adhesive liquid embolic agents (NALEA). In literature, non-adhesive liquid embolic agents have mainly been used in the cerebral district; however, multiple papers describing the use of NALEA in the extracranial district have been published recently and the aim of this review is to explore and analyze this field of application. There are a few NALEA liquids such as Onyx, Squid, and Phil currently available in the market, and they are used in the following applications: mainly arteriovenous malformations, endoleaks, visceral aneurysm or pseudoaneurysm, presurgical and hypervascular lesions embolization, and a niche of percutaneous approaches. These types of embolizing fluids can be used alone or in combination with other embolizing agents (such as coils or particles) so as to enhance its embolizing effect or improve its possible defects. The primary purpose of this paper is to evaluate the use of NALEAs, predominantly used alone, in elective embolization procedures. We did not attempt a meta-analysis due to the data heterogeneity, high number of case reports, and the lack of a consistent follow-up time period.